2018
DOI: 10.3390/nu10121992
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Childhood Picky Eating and Its Relationship to Food Intakes, Nutritional Status, and Growth

Abstract: A main characteristic of children perceived as picky eaters is their tendency to avoid certain foods or food groups. The goal of this narrative review is to provide an overview of published studies that have examined whether picky eating in childhood is in fact associated with measurable differences in food and/or nutrient intakes and growth. While picky eaters appear to consume less vegetables compared to non-picky eaters, no consistent differences were observed for the intakes of other food groups or the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 49 publications
2
77
0
20
Order By: Relevance
“…The mean YHEI total score for this group was nearly 7 points lower than that the mean score for the group with delayed sweets and fruit juice. A recent narrative review examined differences in food and nutrient intakes between children perceived by their parents as picky eaters and those perceived as non-picky eaters and found that only intake of vegetables was lower among picky eaters [35]. Overall diet quality was not compared between the two groups in this review.…”
Section: Discussionmentioning
confidence: 99%
“…The mean YHEI total score for this group was nearly 7 points lower than that the mean score for the group with delayed sweets and fruit juice. A recent narrative review examined differences in food and nutrient intakes between children perceived by their parents as picky eaters and those perceived as non-picky eaters and found that only intake of vegetables was lower among picky eaters [35]. Overall diet quality was not compared between the two groups in this review.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, prolonged breastfeeding and the introduction of food after six months of age tend to act as protective factors. The conduct is mainly aimed at reducing maternal anxiety and continuing to expose the child to food since there is a great possibility that such behavior ceases to manifest itself after the age of seven (Samuel et al 2018).…”
Section: Picky Eating (Pe)mentioning
confidence: 99%
“…The term "picky eating" is an umbrella term used to capture a spectrum of behavioural or appetite traits that are perceived by parents or caregivers as a problematic issue [1,2]. To the best of our knowledge, there is no formally recognized definition of picky eating-also commonly known as Int.…”
Section: Introductionmentioning
confidence: 99%
“…Res. Public Health 2020, 17, 1573 2 of 14 "fussy", "choosy" and "faddy" eating [1]. However, it is generally thought to be characterized by poor dietary variety, eating limited amounts of food, eating slowly, unwillingness to eat familiar or novel foods, and problematic mealtime parent-child relationships [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation